The Climate Change Impact on Agriculture Productivity in Karama Sector, Nyagatare District, Rwanda. - Odile, Twagiramariya (Kabale University, 2019)
A Research Report Submitted in Partial Fulfillment of the Requirements for the award of A Bachelor of Environmental Science of Kabale University